2012
DOI: 10.1371/journal.pone.0032084
|View full text |Cite
|
Sign up to set email alerts
|

Dextran Sodium Sulfate (DSS) Induces Colitis in Mice by Forming Nano-Lipocomplexes with Medium-Chain-Length Fatty Acids in the Colon

Abstract: Inflammatory bowel diseases (IBDs), primarily ulcerative colitis and Crohn's disease, are inflammatory disorders caused by multiple factors. Research on IBD has often used the dextran sodium sulfate (DSS)-induced colitis mouse model. DSS induces in vivo but not in vitro intestinal inflammation. In addition, no DSS-associated molecule (free glucose, sodium sulfate solution, free dextran) induces in vitro or in vivo intestinal inflammation. We find that DSS but not dextran associated molecules established linkag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
182
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 281 publications
(200 citation statements)
references
References 40 publications
11
182
0
1
Order By: Relevance
“…To investigate the role of Hh signaling in IBD, we first tested whether Gli1 inactivation increases the severity of acute dextran sulfate sodium (DSS)-induced colitis in mice (7). We obtained inconclusive results, quite distinct from those previously reported (Fig.…”
Section: Reduction Of Hh Pathway Activity Exacerbates Acute Dss-inducedmentioning
confidence: 85%
“…To investigate the role of Hh signaling in IBD, we first tested whether Gli1 inactivation increases the severity of acute dextran sulfate sodium (DSS)-induced colitis in mice (7). We obtained inconclusive results, quite distinct from those previously reported (Fig.…”
Section: Reduction Of Hh Pathway Activity Exacerbates Acute Dss-inducedmentioning
confidence: 85%
“…Contrary to this and consistent with our findings, Boddicker et al showed that a high-fat lard-based diet (60% kcal from fat) significantly decreased total colonic lesions compared with a LFD in male C57BL/6 mice (5). Of further interest is the study of Laroui et al, whose findings suggest that DSS is responsible for colitis development by forming "nanolipocomplexes" with MCFAs in the colon (27). Other studies have also shown that DSS treatment paired with HFD consumption produces a more aggressive form of colitis than DSS coupled with a LFD (17,29,40,41).…”
Section: Discussionmentioning
confidence: 99%
“…DSS colitis has been attempted using many different mouse strains with varying degrees of success. The current hypothesis of how colitis-inducing injury occurs is that DSS is directly toxic to the gut epithelium (Laroui et al 2012). The loss of epithelial integrity and subsequent migration of bacteria into the crypt results in inflammation and triggers a pathologic loss of structure.…”
Section: Mouse Strainmentioning
confidence: 99%
“…In contrast, disease activity scores such as diarrhea and presence of occult blood are typically not quantitative enough to be meaningfully correlated with pathology (i.e., these are binary readouts) and are not used in balancing cohorts. When available, more sophisticated techniques such as endoscopy can be employed to assess colon damage and group animals (Laroui et al 2012). In contrast to colitis models, ileitis models do not positively correlate with body weight loss, and visualization of the mouse ileum is not possible using endoscopy methods.…”
Section: Randomizationmentioning
confidence: 99%